2016
DOI: 10.18632/oncotarget.9306
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic acid ameliorates colitis in association with increasedAkkermansiapopulation in the gut microbiota of mice

Abstract: Emerging evidence shows that dietary agents and phytochemicals contribute to the prevention and treatment of ulcerative colitis (UC). We first reported the effects of dietary caffeic acid (CaA) on murine experimental colitis and on fecal microbiota. Colitis was induced in C57BL/6 mice by administration of 2.5% dextran sulfate sodium (DSS). Mice were fed a control diet or diet with CaA (1 mM). Our results showed that dietary CaA exerted anti-inflammatory effects in DSS colitis mice. Moreover, CaA could signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
99
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(104 citation statements)
references
References 39 publications
4
99
1
Order By: Relevance
“…In particular, MIMP intervention remarkably increased bacterial diversity and modified the community structure in the colitis mice, as shown by our cluster analysis and PCoA analysis. Specifically, we noticed that MIMP treatment dramatically decreased the abundance of Firmicutes, which were previously shown to be associated with IBD development [36-38]. Likewise, we observed a decreased trend in the abundance of pro-inflammatory microbiota in the MIMP-treated group, such as Lachnospiraceae and Allobaculum [38, 39].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In particular, MIMP intervention remarkably increased bacterial diversity and modified the community structure in the colitis mice, as shown by our cluster analysis and PCoA analysis. Specifically, we noticed that MIMP treatment dramatically decreased the abundance of Firmicutes, which were previously shown to be associated with IBD development [36-38]. Likewise, we observed a decreased trend in the abundance of pro-inflammatory microbiota in the MIMP-treated group, such as Lachnospiraceae and Allobaculum [38, 39].…”
Section: Discussionmentioning
confidence: 55%
“…Specifically, we noticed that MIMP treatment dramatically decreased the abundance of Firmicutes, which were previously shown to be associated with IBD development [36-38]. Likewise, we observed a decreased trend in the abundance of pro-inflammatory microbiota in the MIMP-treated group, such as Lachnospiraceae and Allobaculum [38, 39]. In addition, Leuconostocaceae and Leuconostoc, previously identified probiotics that exert anti-inflammatory effects by inducing IL-10 secretion [40], were enriched in the MIMP-treated group.…”
Section: Discussionmentioning
confidence: 99%
“…Akkermansia is a gram-negative anaerobe belonging to Verrucomicrobia. Akkermansia can produce a large number of enzymes with mucoid degradation 41 , and degrade intestinal mucins, the highly glycosylated proteins of epithelial mucus layer, as its sole source of carbon and nitrogen 42 . Oral administration of Akkermansia can improve blood glucose and fat metabolism to remit the metabolic diseases (such as obesity and type 2 diabetes).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in rodents have shown that oral CaA (1 mmol L −1 d −1 for 15 days) could re‐establish microbiota richness and inhibit the increase of Firmicute‐to‐Bacteroidetes ratio, and could increase the proportion of mucin‐degrading Akkermansia in female C57BL/6 mice (18–20 g) with dextran sulfate sodium (DSS)‐induced colitis . Akkermansia has been extensively studied in relation to its role in the prevention or treatment of obesity and associated metabolic disorders .…”
Section: Hca Interactions With the Gut Microbiotamentioning
confidence: 99%
“…Akkermansia has been extensively studied in relation to its role in the prevention or treatment of obesity and associated metabolic disorders . Moreover, caffeic acid significantly reduced the secretion of the pro‐inflammatory cytokines IL‐6, TNFα and IFNγ, and the colonic infiltration of CD3+ T cells, CD177+ neutrophils and F4/80+ macrophages by inhibiting NF‐κB signaling activation . In humans, 100 mg mL −1 CaA stimulated an increase by a 1–2 log factor in both Bacteroidetes and Firmicutes ( P < 0.005) after 48 h fermentation .…”
Section: Hca Interactions With the Gut Microbiotamentioning
confidence: 99%